Legal Accountability of Parking Service Operators for Motor Vehicle Damage or Loss in Public Roadside Parking - Erryc Save Oka Mamoh; Jimmy Pello; Pius Bere; Daud Yaferson Dollu (Advances in Public Law and Policy, 2026)
Purpose: This study examines the legal accountability of roadside parking operators in Kupang City for damage to or loss of motor vehicles entrusted to their care, and evaluates whether Kupang City Regional Regulation Number 15 of 2011 on Roadside Parking Levies provides adequate legal certainty and justice for parking users.  Research Methodology: The research applies a socio-legal, empirical-juridical method combining statutory, conceptual, and case approaches, drawing on primary police data from the Kupang City Police Resort together with statutory analysis of the Regional Regulation. Results: The Regional Regulation regulates only the collection of parking levies and related administrative and criminal sanctions for non-paying users; it contains no provision assigning liability to parking operators for vehicles damaged or stolen while parked. Between 2014 and 2017, twenty-one motorcycle theft cases were recorded at roadside parking locations within the Kupang City Police jurisdiction, yet operators consistently refused responsibility, commonly relying on standard exoneration clauses printed on parking tickets. Conclusions: Under general civil liability principles and relevant Supreme Court jurisprudence, such exoneration clauses are void, and operators retain a duty of custody that can give rise to civil and, in specific circumstances, criminal accountability. Limitations: The study is confined to one municipality and one regulatory instrument, and relies on secondary police records rather than operator-side data. Contributions: The findings support a concrete recommendation to revise the Regional Regulation to explicitly regulate operator liability, strengthening consumer protection for parking users.